Manajemen Peningkatan Mutu Ketenagaan dan Sumber Daya Manusia (SDM) di Madrasah Aliyah Negeri Pamekasan - Mohammad Thoha (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2017)
The success of an effort is strongly related to the quality of the effort doer. Similarly, the achievement of a school/madrasa is also determined by the manager. If the manager is highly qualified, then the institution will consequently enhance its performance, and vice versa. This article describes the management of human resource quality development in MAN Pamekasan. It focuses on planning, staffing, coaching, staff promotion, mutation, and dismissal as well as evaluation and compensation. By means of observation, interviews, and documentation, it is found that MAN Pamekasan manages staff and other human resources satisfactorily; at least it has achieved the standard stipulated by the government.